(untitled) (Sociologisk Forskning, 1994)
A shift of system with obstacles? To begin with, the article discusses the concepts in the theme of the Swedish Sociological Association’s annual meeting 1994, ”State, market and civil society” . It is argued that the democratic character of the state and its positive role in providing social services should not be underestimated, that the market category tends to make the process of production invisible,and that the ideas about civil society are muddy. Then, the Swedish societal model is described with the help of modified versions of these concepts. It was built upon a compromise between labour and capital and it is characterized by a generous transfer system, a large public service production, a market-oriented but rather regulated capitalist economy,and a comparatively weak civil society. In recent years, neoliberalism has gained ground and reforms have been carried out weakening the role of the state and the public sector. However, the alleged positive results of the shift of system have not appeared and this is no doubt a problem for those advocating such reforms. The process may nevertheless continue, since the prerequisites of the compromise between labour and capital have been undermined with, among other things, the growing internationalization of the economy.